Estudios de casos sobre cambio tecnológico en la producción de frijol en América Latina - Pachico, Douglas H. (International Center for Tropical Agriculture, 1987)
Case studies of Costa Rica, Guatemala, and Colombia on the adoption of improved technology were reviewed to (1) determine to what extent technology has been adapted to the needs of farmers with limited resources, (2) analyze the relationship between adoption of new varieties and changes in farm management, and (3) examine the socioeconomic and institutional context as a determinant factor of opportunities for technological change. The impact of new technology is critically related to the effectiveness of seed production and distribution, market points, extension, and on-farm research. Improved technology for farming systems should be designed on the basis of site-specific biotic and socioeconomic characteristics. Case studies of bean farmers in marginal areas, where a disease resistance strategy was applied, indicate that bean production can be improved outstanding example is the case of Costa Rica, where production doubled in the 1980s